The Impact of Corporate Characteristics on Sustainability Reporting Listed in the Colombo Stock Exchange - Madushan, M.M.V.; Karunarathna, W.V.A.D. (Department of Accountancy, Faculty of Commerce and Management Studies, University of Kelaniya Sri Lanka, 2023)
The term “corporate sustainability” describes a new corporate management model. These include the linkages between environmental, social, and economic issues as well as long-term perspectives. The goal is to provide long-term value for stakeholders without compromising people, the planet, or the economy. This study investigates the impact of determinants on corporate sustainability reporting (CSR) disclosure. While many studies have investigated sustainability reporting in developed countries, there is a dearth of research in the context of developing countries. As a developing country in the Sri Lankan context, it was confirmed that a few times the researchers gave comparatively less attention to investigating the impact of firms’ specific determinants on sustainability reporting disclosures. Thus, the study aimed to investigate the impact of firm characteristics on corporate sustainability reporting in Sri Lanka related to listed companies. In the study, the firm’s age, firm size, Leverage, and Firm profitability, are considered independent variables. Those variables are measured by using the total asset, the number of listed years, Total debt to total asset ratio, and Return on equity. The dependent variable of CSR was measured by using the Global Reporting Initiatives (GRI) index. Consequently, these quantitative data were employed in the panel data regression model using E- Views software to scientifically analyze the data to identify the significant relationship between these two variables. This study documents that firm size and leverage are positively associated with sustainability reporting and firm age, negatively associated with CSR, and profitability is not significantly associated with SR in the Finance sector. Leverage, firm age, and firm size are positively associated with SR while profitability is negatively associated with SR. This study helps the shareholders vi and investment community evaluate the firm and make the optimum decisions. Furthermore, the management can also get knowledge for making decisions and making differences by getting efficient outcomes from that.
Keywords: CSR, Finance Sector, GRI, Sri Lanka, Dependent Variable and Independent Variables